Penerapan Metode Simple Additive Weighting pada Sistem Pendukung Keputusan Pemilihan Raket Bulu Tangkis - Saragih, Ahmad Fadhly Sani; Muhammad Ikhsan; Lubis, Aidil Halim (Universitas Harapan Bangsa, 2025)
Badminton is one of the most popular sports in Indonesia and a source of national pride due to the achievements of its athletes in international tournaments. The racket is the primary equipment used in badminton, and selecting the appropriate one is crucial for performance and comfort. However, many beginner players still find it difficult to choose a suitable racket according to the coach’s recommendation. Therefore, this study developed a Decision Support System (DSS) for badminton racket selection by applying the Simple Additive Weighting (SAW) method. Four alternatives—Yonex, Li-Ning, Flypower, and Victor—were evaluated using five criteria: price, racket weight, head type, shaft flexibility, and handle size. The integration of the SAW method into a web-based application produced ranking results for racket selection. The results showed that Li-Ning G Force Superlite 3900 achieved the highest score of 0.8845, indicating it as the most suitable racket for beginner players.